PREDICTORS OF PERFORMANCE IN THE LICENSURE EXAMINATION FOR BTTE GRADUATES OF ONE STATE COLLEGE IN THE PHILIPPINES - JOSE ARIEL IBARRIENTOS (Journal of English Education and Linguistics, 2022)
The study was conducted to identify the performance of the Bachelor of Technical Teacher Education (BTTE) graduates of Camarines Sur Polytechnic Colleges and to develop a statistical model that may be adopted by the department in predicting ratings in the teacher’s licensure examination. The study used a quantitative-descriptive method in the analysis of the grades of the 85 students gathered from several secondary sources. The correlational method was used to explore the predictors of performance in the licensure examination graduates who took the licensure examination. Pearson’s correlation and multiple regression were used to analyze the licensure examination ratings, college admission test, and academic performance of 85 respondents. Findings revealed that most students have lower results in the College Admission Test yet have Good to Very Good results in academic performance. Furthermore, students attained fairly good performance in their LET. Based on the findings of the study, academic performance is a good predictor of the graduate’s achievement in the licensure examination. Thus, a regression model was developed and may be adopted by the department in predicting ratings in the teacher’s licensure examination.